Human cytomegalovirus UL82 promotes cell cycle progression of colorectal cancer by upregulating AGR2 - Haitao Ren; Bing Wang; Lanni Wang; Ye Shi; Ruini Li; Chaoyi Jiang; Jingxin Feng; Jiahao Wang; Hanru Yao; Linhua Lan; Guohui Gao; Liyi Li; et al. (Communications Biology)
Abstract The correlation between persistent human cytomegalovirus (HCMV) infection and poor prognosis in colorectal cancer (CRC) patients has garnered increasing attention. UL82 is a tegument protein of HCMV, and our previous research indicated that the presence of UL82 is significantly associated with reduced overall survival in CRC patients. However, the mechanism by which UL82 affects the prognosis of CRC patients remains unclear. In this study, we investigated the role of UL82 in CRC progression through both in vitro and in vivo experiments, and revealed its downstream regulatory pathways by integrating transcriptomics, metabolomics, and proteomics. Our findings first revealed that UL82 significantly promoted CRC cell proliferation by increasing the proportion of cells in the S phase of the cell cycle. Additionally, UL82 enhanced the expression of the oncogene AGR2, while knockdown of AGR2 abolished the proliferative effect of UL82. Interestingly, UL82 interacted with the transcription factor DDX5, which transcriptionally inhibited AGR2 expression. Furthermore, this UL82-AGR2 axis promoted nucleotide metabolism in CRC cells by enhancing the levels of nucleotide synthesis enzymes DTYMK, RRM2, and TYMS. In conclusion, our study suggests that the UL82/DDX5 complex may promote nucleotide metabolism and cell cycle progression of CRC by upregulating AGR2 and UL82 may serve as a potential prognostic biomarker for CRC patients.